Прогнозування зон аномально високого пластового тиску методом d-експоненти в реальному часі буріння свердловин з використанням ЕОМ - Олексюк, М.П.; Юрич, А.Р.; Різничук, А.І. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
The article describes the nature of d-exponent method and manner of its implementation on a computer to select the areas AHPP in real time directly to wells deepening “press in” are found out. Advantages of new construction are set.